Globale Entwicklung – Entwicklung und Nachhaltigkeit - Böhn, Dieter (STUDIUM EDUCATIONIS - Rivista semestrale per le professioni educative, 2014)
“Environment” and “Development” (in the context of developing countries) have been standard topics of geographical education in Germany for decades, albeit with many different examples. An “orientation framework” integrates both of these topics in the context of sustainability. 11 competencies from the fields “Recognize”, “Evaluate” and “Act” are presented in a matrix that includes 20 different topics, of which all can possibly include “sustainable development”. For the individual school subjects, i.e. Geography as well, special competencies and topics have been formulated that are then cultivated using specific content. In addition to this “framework”, there are also many other different topics in geographical education for sustainability. Pupils learn to act responsibly so as to protect nature. For example, they reflect on the Agenda 21 in classroom discussions and learn how citizens can act on a local scale through initiatives. Instruction also shows how we can use modern technologies on a wider scale (regional to global) to integrate sustainable utilization of resources and economic development.